Diverse Presentation of Meckel’s Diverticulum in Pediatric Patients - Kumar, Sujit; Jalan, Aditya; Patowary, Bhupendranath; Gurung, Sarita Rana; Belbase, Narayan; Mahaseth, Subhash (Journal of College of Medical Sciences-Nepal, 2018)
Introduction Meckel’s Diverticulum is the most common congenital disease and seen in 2% of population. It is difficult to diagnose preoperative, mostly seen during operation with its various presentation. Material and Methods This is a retrospective study in which all the cases diagnosed as Meckel’s diverticulum with its complication diagnosed while doing operation were included. Demographic data, clinical presentation, preoperative diagnosis, intraoperative findings, surgical procedure performed, histopathological report and postoperative follow up of patients were recorded and statistically analyzed. The aim of this study was to assess various presentation of Meckel’s diverticulum in 8 years of duration in college of medical sciences, Bharatpur Nepal. Results Out of 32 cases, there were 20 male and 12 female with M:F ratio1.66:1. The mean age was 8.34 ± 3.98 years. All together sixteen (50%) patients had features intestinal obstruction. Perforation was seen in 28.1% patients, intussusception in 21.8%, diverticulitis in 15.6%, small bowel volvulus around fibrous band in 18.8%, internal herniation in 9.4% and massive bleeding in 6.3% patients. The average distance from ileocecal junction was 40-60 cm. All cases underwent emergency laparotomy, presence of Meckel’s diverticulum was incidental intraoperative finding. Three cases had superficial wound infection. Small intestine mucosa followed by gastric, pancreatic and colonic mucosa were most common histological finding. The average duration of hospital stay was 5 to 8 days. Conclusion Meckel's Diverticulum is a true diverticular anomaly that may remain clinically silent for lifetime, or it may have life-threatening complications. Due to nonspecific features in case of acute abdomen, Meckel’s diverticulum and its complications should be kept as an important differential diagnosis. Keywords: intestinal obstruction; meckel’s diverticulum; volvulus.